Avatars in Pain: Visible Harm Enhances Mind Perception in Humans and Robots. (December 2018) - Swiderska, Aleksandra; Küster, Dennis
Previous research has shown that when people read vignettes about the infliction of harm upon an entity appearing to have no more than a liminal mind, their attributions of mind to that entity increased. Currently, we investigated if the presence of a facial wound enhanced the perception of mental capacities (experience and agency) in response to images of robotic and human-like avatars, compared with unharmed avatars. The results revealed that harmed versions of both robotic and human-like avatars were imbued with mind to a higher degree, irrespective of the baseline level of mind attributed to their unharmed counterparts. Perceptions of capacity for pain mediated attributions of experience, while both pain and empathy mediated attributions of abilities linked to agency. The findings suggest that harm, even when it appears to have been inflicted unintentionally, may augment mind perception for robotic as well as for nearly human entities, at least as long as it is perceived to elicit pain.